Measurement Instruments and Software Used in Biotribology Research Laboratory - Tyurin, Andrei; Ganus, German; Stepanov, Mikhail; Ismailov, Gafurzhan (Electrical, Control and Communication Engineering, 2015)
Precision measurements of friction processes have a key role in a variety of industrial processes. The emergence of fine electronic circuit techniques greatly expands capabilities of control. There are some difficulties for their full implementation today, especially when it regards the accuracy and frequency of measurements. The motion-measuring method in real-time system is considered in this article, paying special attention to increased accuracy. This method is based on rapid analog digital converter (ADC), transmission program and digital signal processor (DSP) algorithms. Description of laboratory devices is included: Tribal-T and universal friction machine (MTU-01) designed for “Pin on disc” tests. Great emphasis is placed on the usability of accelerometers. The present study examined the collected data via laboratory system for data acquisition and control, and processing it in the laboratory of Biotribology. Laboratory supervisory control and data acquisition (SCADA) algorithms is described below. Task of regulation is not considered. This paper describes only methods of automatic control theory to analyze the frictional quality.